Review of World Bank Support for Student Assessment Activities in Client Countries, 1998-2009 - Liberman, Julia (World Bank, Washington, DC, 2014)
As more and more countries both developed and developing have become interested in collecting information on student learning, there has been a concomitant growth in the demand for strong student assessment systems. The World Bank is at the forefront of efforts to support developing countries in the strengthening of their student assessment systems. This paper provides an overview of the World Banks support for assessment activities in its client countries between 1998 and 2009. The paper highlights key lessons learned from this experience and offers guidance to development staff and country teams for the more effective design and implementation of assessment activities in education projects.